Study of the persistence and dynamics of recombinant mCherry‐producing Yarrowia lipolytica strains in the mouse intestine using fluorescence imaging. Issue 3 (20th December 2022) - Madzak, Catherine; Poiret, Sabine; Salomé Desnoulez, Sophie; Foligné, Benoit; Lafont, Frank; Daniel, Catherine
Abstract: Yarrowia lipolytica is a dimorphic oleaginous non‐conventional yeast widely used as a powerful host for expressing heterologous proteins, as well as a promising source of engineered cell factories for various applications. This microorganism has a documented use in Feed and Food and a GRAS (generally recognized as safe) status. Moreover, in vivo studies demonstrated a beneficial effect of this yeast on animal health. However, despite the focus on Y. lipolytica for the industrial manufacturing of heterologous proteins and for probiotic effects, its potential for oral delivery of recombinant therapeutic proteins has seldom been evaluated in mammals. As the first steps towards this aim, we engineered two Y. lipolytica strains, a dairy strain and a laboratory strain, to produce the model fluorescent protein mCherry. We demonstrated that both Y. lipolytica strains transiently persisted for at least 1 week after four daily oral administrations and they maintained the active expression of mCherry in the mouse intestine. We used confocal microscopy to image individual Y. lipolytica cells of freshly collected intestinal tissues. They were found essentially in the lumen and they were rarely in contact with epithelial cells while transiting through the ileum, caecum and colon of mice. Taken as a whole, our results have shown that fluorescent Y. lipolytica strains constitute novel tools to study the persistence and dynamics of orally administered yeasts which could be used in the future as oral delivery vectors for the secretion of active therapeutic proteins in the gut. Abstract : Yarrowia lipolytica is a dimorphic oleaginous non‐conventional yeast widely used as a powerful host for expressing heterologous proteins. To study its potential for oral delivery of recombinant therapeutic proteins in mammals, we engineered two Y. lipolytica strains to produce the model fluorescent protein mCherry. We demonstrated that both Y. lipolytica strains transiently persisted in mice after four daily oral administrations and they maintained the active expression of mCherry in the mouse intestine. We used confocal microscopy and showed that Yarrowia cells were found essentially in the lumen and they were rarely in contact with epithelial cells while transiting through the ileum, caecum, and colon of mice. Taken as a whole, our results have shown that fluorescent Y. lipolytica strains constitute novel tools to study the persistence and dynamics of orally administered yeasts.